Firm size and innovation in European manufacturing - Andrea Vaona; Mario Pianta (Kiel Institute for the World Economy (IfW), 2006)
The paper investigates the differences between small, medium-sized and large firms regarding their performance in the introduction of new products and processes. After a review of the relevant literature, two models are proposed and tested in search for different business strategies and innovation inputs connected to product and process innovations. The empirical analysis uses innovation survey (CIS 2) data at the industry level for 22 manufacturing sectors, broken down in three firm size classes, for eight European countries. Special attention is devoted to tackling the issues of possible endogeneity of the regressors and of unobserved sectoral heterogeneity. The results - strengthening the findings of previous studies - show that product and process innovations, though having some complementarities, are associated to different innovative inputs and strategies pursued by firms. Systematic differences also emerge between the behaviour of large firms and SMEs.
Keywords: L11; O31; O33; 330; Process innovation; Firm size; Determinants of innovation; European industries; Product innovation; Innovation; Betriebsgröße; Verarbeitendes Gewerbe; Schätzung; EU-Staaten